Pembentukan Karakter Gemar Menabung dan Kreatif Anak Sekolah Dasar Melalui Inovasi Celengan Daur Ulang - Sonya Nurizki Vikandari; Aiman Fisabilah; Pandu Pratama; Randi Arya Dira; Nurul Rohmatilah; Ana Lisnawati; Dona Fauzi Romadona (Universitas Perjuangan Tasikmalaya, 2026)
A common problem among elementary school-aged children is a lack of awareness of the importance of saving and a low level of environmental awareness. These two principles need to be instilled early on to foster a thrifty and responsible attitude towards the environment. This community service activity aims to educate students about the importance of saving while fostering creativity and environmental awareness through the creation of piggy banks from used materials. This program is a collaboration between students from the Community Service Program (KKN) in Cimanggu Village and SDN Handeuar, which took place from July 22 to August 26, 2025. The activity included outreach, demonstrations, and hands-on practice in creating piggy banks using used materials such as cans and cardboard. The results showed that students were very enthusiastic and were able to create various unique piggy bank designs and understand the concept of saving and utilizing used materials more deeply. This activity not only increases awareness of saving but also fosters creativity and environmental awareness from an early age. Therefore, this program can be an effective and sustainable educational tool in developing environmental awareness and a love of saving in elementary school children.